Diagnostic value of full-mouth radiography in horses - Bishop, Ian Tyler (Frontiers in Veterinary Science, 2022)
In this observational study, oral examinations and full-mouth dental radiographs were performed on 248 horses presented for routine oral health care. The findings were assessed to determine how often disease was diagnosed by radiographs without having related findings on oral examination. In 50 horses (20%), there were radiographic signs of disease that would not have been predicted based upon the oral examination. 113 horses (46%) had oral examination findings that would have prompted dental radiography, according to the criteria of the study. Of these 113 horses, 24 (21%) had radiographic signs of disease that would have been missed if only targeted radiographs had been taken, rather than a full-mouth survey.